Low-cost web-based greenhouse monitoring system using NodeMCU ESP8266 - Muhammad Faizzul, Ahmam (2019)
Agriculture is a very important sector that we need to take care of since it gives benefits to human kinds and civilization. There are many challenges need to face to maintain the agriculture products. Greenhouse is a part of effort to produce agriculture product that can be use. However, it is challenging to take care of those crops inside the greenhouse to ensure it can produce high quality product. The problem statements are the farmer must manually water their plant, cannot control the greenhouse temperature and lack of greenhouse security. The objective of this project is to study current greenhouse monitoring system, to design and develop greenhouse monitoring system and to evaluate the functionalities of the greenhouse monitoring system. Low-Cost Web-Based Greenhouse Monitoring System Using NodeMCU ESP8266 is a system to helps the farmer to monitor the basic needs of their crops in the greenhouse to produce better quality agriculture product. This system uses NodeMCU ESP8266 to send sensors readings which are temperature, soil humidity and light intensity by using HTTP to communicate with the server of the system to be processed in the web applications. At the end of this project, the developer found out that this system able to help the farmer in monitoring their crops in the greenhouse and effective in monitoring the crops. In conclusion, this system able to provide solution to farmer in monitoring their greenhouse.